The urgent need for more potent antiretroviral therapy in low-income countries to achieve UNAIDS 90-90-90 and complete eradication of AIDS by 2030 - Emmanuel Ndashimye; Eric J. Arts (BMC, 2019)
Abstract Background Over 90% of Human Immunodeficiency Virus (HIV) infected individuals will be on treatment by 2020 under UNAIDS 90-90-90 global targets. Under World Health Organisation (WHO) "Treat All" approach, this number will be approximately 36.4 million people with over 98% in low-income countries (LICs). Main body Pretreatment drug resistance (PDR) largely driven by frequently use of non-nucleoside reverse transcriptase inhibitors (NNRTIs), efavirenz and nevirapine, has been increasing with roll-out of combined antiretroviral therapy (cART) with 29% annual increase in some LICs countries. PDR has exceeded 10% in most LICs which warrants change of first line regimen to more robust classes under WHO recommendations. If no change in regimens is enforced in LICs, it's estimated that over 16% of total deaths, 9% of new infections, and 8% of total cART costs will be contributed by HIV drug resistance by 2030. Less than optimal adherence, and adverse side effects associated with currently available drug regimens, all pose a great threat to achievement of 90% viral suppression and elimination of AIDS as a public health threat by 2030. This calls for urgent introduction of policies that advocate for voluntary and compulsory drug licensing of new more potent drugs which should also emphasize universal access of these drugs to all individuals worldwide. Conclusions The achievement of United Nations Programme on HIV and AIDS 2020 and 2030 targets in LICs depends on access to active cART with higher genetic barrier to drug resistance, better safety, and tolerability profiles. It's also imperative to strengthen quality service delivery in terms of retention of patients to treatment, support for adherence to cART, patient follow up and adequate drug stocks to help achieve a free AIDS generation.